Girl Of The Shining Mountains - Peter Roop (Roop Books, 1999)
"Mama, tell me about your journey to the great salt lake, the Pacific Ocean."
Droits : Source Google Books a verifier
Keywords: Stephen King; Vintage; fiction; horror fiction; Recherche bibliographique; shining; york; times; bestseller; time; best; mystery; thriller; books; masterpiece; modern; american; horror; inspired; stanley; kubrick; classic; film; jack; histoire; Fiction